PENGADAAN ECO-LIBRARY BERBASIS PENGELOLAAN SAMPAH DI DESA KILENSARI KECAMATAN PANARUKAN KABUPATEN SITUBONDO JAWA TIMUR - Endang Suhesti; Siti Muyasaroh (INTEGRITAS : Jurnal Pengabdian, 2018)
This activity was aimed to solve the problems related to the lack of awareness and understanding of the community in Kilensari Village, Panarukan Subdistrict on proper waste management. Based on preliminary observations, people dump garbage around the river mouth area. It caused environmental degradation, threats to aquatic organisms, and risks to human health. To overcome this, the proposed establishment of eco-library as a means of education and socialization to the community for better waste management. The establishment of an eco-library involves NGOs engaging in environmental literacy, Greenbooks.org. This NGO acts as an online instructor on environmental education activities provided. Based on interviews with Head of Kilensari Village, there has been a plan for making temporary garbage collection (TPS) in Kilensari Village which will be built in 2018 with total area of ± 3Ha. The socialization of eco-library was held on 15 November 2017 at Kilensari Village Hall, Panarukan Sub-district. Communities participating in the socialization activities were quite enthusiastic about the establishment of an eco-library and a plan of cooperation with Greenbooks.org for environmental learning for children. It is hoped that socialization and training activities related to waste management can continue, so that people understand and implement waste management properly. Initially, the eco-library was proclaimed to have a collection of waste management-based books targeting children's readers aged 6-18. But as the program progresses, the books are not specially discussed about waste management, but still themed environment and living creatures. Cooperation with Greenbooks.org will begin with registration of eco-library in Kilensari Village.